Difficult men [strategies for women who choose not to leave] - Melville, Arabella (1998)
This text examines the taboo subject of violent men. Drawing on her own experience of living with such an individual, Arabella Melville explores the alternatives to the conventional wisdom which says you must leave an abusive man - showing how women can succeed in relationships with difficult men.